2012
DOI: 10.1038/onc.2012.408
|View full text |Cite
|
Sign up to set email alerts
|

CIB1 prevents nuclear GAPDH accumulation and non-apoptotic tumor cell death via AKT and ERK signaling

Abstract: CIB1 is a 22-kDa regulatory protein previously implicated in cell survival and proliferation. However, the mechanism by which CIB1 regulates these processes is poorly defined. Here we report that CIB1 depletion in SK-N-SH neuroblastoma and MDA-MB-468 breast cancer cells promotes non-apoptotic, caspase-independent cell death that is not initiated by increased outer mitochondrial membrane permeability or translocation of apoptosis-inducing factor to the nucleus. Instead, cell death requires nuclear GAPDH accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 54 publications
9
48
1
Order By: Relevance
“…CIB1 is a small intracellular protein that regulates kinase activity and integrin biology [1016], and has an emerging role in cancer cell survival and proliferation via regulation of oncogenic signaling pathways [10, 12, 14, 17, 18]. For example, CIB1 promotes AKT and ERK activation [10, 19], and may regulate these pathways via interaction with the serine/threonine kinase PAK1 [11, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIB1 is a small intracellular protein that regulates kinase activity and integrin biology [1016], and has an emerging role in cancer cell survival and proliferation via regulation of oncogenic signaling pathways [10, 12, 14, 17, 18]. For example, CIB1 promotes AKT and ERK activation [10, 19], and may regulate these pathways via interaction with the serine/threonine kinase PAK1 [11, 20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, CIB1 promotes AKT and ERK activation [10, 19], and may regulate these pathways via interaction with the serine/threonine kinase PAK1 [11, 20]. We recently showed that CIB1 depletion in two cancer cell lines (SK-N-SH neuroblastoma and MDA-MB-468 TNBC) disrupted both AKT and ERK signaling, resulting in the induction of a DNA damage response and a unique mechanism of non-apoptotic cell death [10]. …”
Section: Introductionmentioning
confidence: 99%
“…CIB1 binds to a number of potential effectors, such as PKD2 [18], AKT, ERK [19], PAK1 [20], PLK3 [21,22], and the functions of some of these proteins have been shown to be influenced by CIB1. These studies suggest that CIB1 regulates tumor growth, cell migration, endomitosis, and cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has suggested that CIB1 perform important roles in cell survival, cell proliferation, cell apoptosis and cell migration, thereby mediating tumor growth and angiogenesis [17, 20, 39-43]. CIB1 may serve an important role in tumorigenesis by regulating several kinase partners or oncogenic signaling (Table 1, 2 and Fig.…”
Section: The Potential Roles Of Cib1 In Tumor Progressionmentioning
confidence: 99%
“…CIB1 is also implicated in cell survival and proliferation by modulating PI3K/AKT and MEK/ERK oncogenic signaling [41, 42]. Leisner et al have been identified that CIB1 depletion increased nuclear distribution of GAPDH by interrupting AKT and ERK signaling leading to caspase-independent cell death and proliferation inhibition [43]. Besides, CIB1 can associate with the catalytic subunit of human telomerase reverse transcriptase (hTERT), stimulating telomerase activity and telomere lengthening [53, 54].…”
Section: The Potential Roles Of Cib1 In Tumor Progressionmentioning
confidence: 99%